EVALUATION AND SELECTION OF SOFTWARE TOOLS OF MODERN IT PROJECT MANAGEMENT SYSTEMS - Я. О. Поволоцький; Р. Р. Усенко (Вісник Черкаського державного технологічного університету, 2018)
The issue of providing information needs of project manager requires special attention. The choice of the optimal software tool is very important in IT project management systems. Over time, projects are becoming more complex, performed in different parts of the globe. Project manager analyzes a huge amount of information and makes decisions. It is proposed to evaluate and select the software tools of modern information technology project management systems based on the substantiation and study of quality criteria, such as crossplatform, reliability, versatility, interface intuition and price. The basic stages of the formation of integrated criterion of evaluation of software are presented. The effective management of a project in the field of information technology depends on the organization and planning of processes in projects, including the presentation of information in a userfriendly form of guidance. The choice of software for IT project management systems is based on the study of software evaluation criteria that are interconnected. When choosing a software tool in the IT management system, it is necessary to consider quality indicators from the point of view of a user, that is, project manager. This approach ensures effective management of IT project and reduces overutilization of resources in the project as well as time. The given research gives an opportunity to provide the choice of the optimum software in the systems of management of IT project. Conclusions are made about the possibility of improving the management of the project in terms of resource, budget and time constraints.